Immunomodulatory and anti-inflammatory properties of macrolides - Bulska Magdalena (Current Issues in Pharmacy and Medical Sciences, 2014)
Macrolides are a group of antibiotics whose activity is ascribable to the presence of the macrolide ring, to which one or more deoxy sugars may be attached. Two properties are inherent in this group of antibiotics, the immunomodulatory and the anti-inflammatory actions, ensuring great efficacy in a wide spectrum of infections. Macrolides demonstrate several immunomodulatory activities both in vitro and in vivo. They can down-regulate prolonged inflammation, increase mucus clearance, prevent the formation of bacterial biofilm and either enhance or reduce activation of the immune system. According to given properties and exceptional effects on bacterial phatogens, the macrolide antimicrobial agents have been found to serve a unique role in the management of chronic airway disorders, including diffuse panbronchiolitis, cystic fibrosis and chronic obstructive pulmonary disease. Use of macrolides can result in clinical improvement in patients with severe, chronic inflammatory airway diseases, improving their spirometry indicators, gas exchange and overall quality of life.